Social Entrepreneurship Competence of Non-formal Education Managers for the Empowerment of Learning Communities - Irvansyah, Adi; Muljono, Pudji; Fatchiya, Anna; Sadono, Dwi (Universitas Negeri Semarang, 2023)
Non-formal education managers who possess social entrepreneurship competence are equipped with the skills and knowledge needed to identify and address social and economic challenges and create innovative and impactful programs that can help improve the lives of the communities they serve. Social entrepreneurship competence involves skills related to leadership, problem-solving, innovation, and community engagement, as well as understanding the social, economic, and cultural factors that can impact non-formal education programs. By developing social entrepreneurship competence, non-formal education managers can create more effective and sustainable programs and better serve the needs and interests of their communities. This study uses a quantitative approach to the survey method. The population of this study is non-formal education managers consisting of study groups, course and training institutions, and community learning activity centers. The research sample and respondents were selected by non-random sampling with 53 respondents. Analysis of data using path analysis. The study suggests a correlation between a manager's character and social competence in entrepreneurship. In addition, this research reveals that management competence is closely related to empowering the community and developing social entrepreneurial skills.